Linguistic Communication and Its Role in Developing Language Skills "Listening Skill As A Model": LINGUISCTICS OF COMMUNICATION - Hazem H. H. Qeshta, (Al-Ḍād Journal, 2022)
This study aims to identify linguistic communication and its role in developing language skills “listening skill as a model.” The research included an important problem with educational dimensions in achieving effective linguistic communication between the teacher and his students, and the ability to know the strengths and weaknesses that students suffer from when communicating with others. We have referred to the concept of linguistic communication through which information and ideas are transferred between individuals, considering communication an essential part linked to human life. Without linguistic communication, we cannot achieve any specific goal or goal, in addition we touched on the skill of listening as the first of the important language skills, which is a receptive skill, the role of this skill in the linguistic communication process and the role of the teacher in it, and the steps and methods of teaching this skill, in order to enrich the students’ language from using this skill in the communication process. daily. Keywords: language communication, language skills, listening skill.